Self-Reduction Behavior of Bio-Coal Containing Iron Ore Composites - Asmaa A. El-Tawil; Hesham M. Ahmed; Lena Sundqvist Ökvist; Bo Björkman (Metals, 2020)
The utilization of CO2 neutral carbon instead of fossil carbon is one way to mitigate CO2 emissions in the steel industry. Using reactive reducing agent, e.g., bio-coal (pre-treated biomass) in iron ore composites for the blast furnace can also enhance the self-reduction. The current study aims at investigating the self-reduction behavior of bio-coal containing iron ore composites under inert conditions and simulated blast furnace thermal profile. Composites with and without 10% bio-coal and sufficient amount of coke breeze to keep the C/O molar ratio equal to one were mixed and Portland cement was used as a binder. The self-reduction of composites was investigated by thermogravimetric analyses under inert atmosphere. To explore the reduction progress in each type of composite vertical tube furnace tests were conducted in nitrogen atmosphere up to temperatures selected based on thermogravimetric results. Bio-coal properties as fixed carbon, volatile matter content and ash composition influence the reduction of iron oxide. The reduction of the bio-coal containing composites begins at about 500 °C, a lower temperature compared to that for the composite with coke as only carbon source. The hematite was successfully reduced to metallic iron at 850 °C by using bio-coal, whereas with coke as a reducing agent temperature up to 1100 °C was required.